Analisis Video Wawancara Alasan Keengganan Untuk Menikah di Jepang - Siahaan, Karin; Arfianty, Rani (Undiksha Press, 2024)
The purpose of this research is to analyze three data through video interviews available on the internet, providing an understanding of individuals’ views and experiences regarding the reluctance to marry in Japan relating to the economy, gender roles and changing of lifestyle preferences. The research method used is qualitative with a listening and note-taking approach via videos available on the internet. The result of this research shows that, although the Japanese government has launched various initiatives, such as subsidies, financial support and funding of matchmaking agencies, factors such as financial worries, gender inequality and changing of lifestyle preferences remains as challenges that needs to be overcome to motivate more people to get married in Japan.